Efektivitas E-Modul Fisika Interaktif Berbasis PBL dalam Meningkatkan Keterampilan Berpikir Kritis dan Kreatif (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to systematically examine the use of interactive physics e-modules based in Problem-Based Learning (PBL) in improving students’ critical and creative thinking skills. The research method employed a Systematic Literature Review (SLR) following the PRISMA protocol. Literature search was conducted through online databases such as Google Scholar, Garuda, OneSearch, and Publish or Perish using keywords: “interactive e-module”, “problem-based learning”, “students’ critical thinking”, “students’ creative thingking”, and “physics learning media”. After applying inclusion-exclusion criteria, 30 relevant articles were selected for analysis. The findings indicate that PBL-based e-modules are effective in enhancing higher-order thinking skills, particularly in analyzing problems, providing logical arguments, and generating innovative solutions. Moreover, interavtive e-modules contribute significantly to increasing student motivation and active participation during the learning process. Therefore, the use of PBL-based interactive physics e-modules can serve as a strategic alternative for educational innovation in the digital era, especially in fortering students’ critical and creative thinking abilities.